The components of diabetes educator's competence in diabetes self-management education in Iran: A qualitative study - Fahimeh Kashani; Parvaneh Abazari; Fariba Haghani (Wolters Kluwer Medknow Publications, 2021)
BACKGROUND: Limited research has been conducted in the field of diabetes educator's competency. However, no comprehensive and integrated explanations of educator's competence requirements in treatment centers exist in Iran. The aim of this study is to explain the components of diabetes educator's competence in diabetes self-management education in Iran. MATERIALS AND METHODS: This was a qualitative descriptive-exploratory study. The data were collected through semi-structured and in-depth interviews and using purposeful sampling method in Isfahan University of medical science from April to October 2018. Sampling continued until data saturation. Participants included 20 people who were selected by purposive and snowball sampling method. The interviews were analyzed using content analysis method of Graneheim, Lundman. RESULTS: Data analysis resulted in the emergence of three main categories including (1) Patient and family centered education, (2) process-based education, and (3) continuous progress in profession and also seven subcategories (patient and family activation, empower), facilitating educational process, comprehensive education assessment, development, implementation and evaluation of educational plans, developing educators' educational knowledge and skills, development of creativity and innovation, promote inter-professional cooperation in education. CONCLUSION: The evaluation of facilitation factors for participation and empowerment patient and family along with creativity and interprofessional collaboration for comprehensive evaluation of patients in designing, implementation of educational programs were mentioned as important competencies of diabetes educators, which can have a significant impact on patients' recovery, treatment, and the promotion of society's health.